Cognitive function and living situation in COPD: is there a relationship with self-management and quality of life? - Dulohery, Megan M (Int J Chron Obstruct Pulmon Dis, 2015)
BACKGROUND: Cognitive impairment is increasingly being found to be a common comorbidity in chronic obstructive pulmonary disease (COPD). This study sought to understand the relationship of comprehensively measured cognitive function with COPD severity, quality of life, living situation, health care utilization, and self-management abilities. METHODS: Subjects with COPD were recruited from the outpatient pulmonary clinic. Cognitive function was assessed using the Montreal Cognitive Assessment (MOCA). Self-management abilities were measured using the Self Management Ability Score 30. Quality of life was measured using the Chronic Respiratory Disease Questionnaire. Pearson correlation was used to assess the bivariate association of the MOCA with other study measures. Multivariate analysis was completed to understand the interaction of the MOCA and living situation on COPD outcomes of hospitalization, quality of life, and self-management ability. RESULTS: This study included 100 participants of mean age 70±9.4 years (63% male, 37% female) with COPD (mean FEV(1) [forced expiratory volume in 1 second] percentage predicted 40.4±16.7). Mean MOCA score was 23.8±3.9 with 63% of patients having mild cognitive impairment. The MOCA was negatively correlated with age (r=−0.28, P=0.005) and positively correlated with education (r=+0.24, P=0.012). There was no significant correlation between cognitive function and exacerbations, emergency room (ER) visits, or hospitalizations. There was no association between the MOCA score and self-management abilities or quality of life. We tested the interaction of living situation and the MOCA with self-management abilities and found statistical significance (P=0.017), indicating that individuals living alone with higher cognitive function report lower self-management abilities. CONCLUSION: Cognitive impairment in COPD does not appear to be meaningfully associated with COPD severity, health outcomes, or self-management abilities. The routine screening for cognitive impairment due to a diagnosis of COPD may not be indicated. Living alone significantly affects the interaction between self-management abilities and cognitive function.